2022
DOI: 10.1371/journal.pone.0268681
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and teachers’ fairness behavior: The mediating role of moral obligation and moderating role of social value orientation

Abstract: This study examined the mediating effect of moral obligation and moderating effect of social value orientation on the relationship between empathy and fairness behavior in Chinese teachers. Seven hundred and twenty-six Chinese teachers completed self-reported questionnaires regarding empathy, moral obligation, social value orientation, and fairness behavior. The results revealed that moral obligation mediated the link between empathy and teachers’ fairness behavior. Teachers’ social value orientation moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In a multi-country study by Barker et al (2022), conducted on behaviour of nurses towards patients, the authors discovered that the nurses with the best clinical outcomes were those who reported the highest levels of empathy. In addition, a study on empathy of teachers and their fair behaviour with school students shows that empathy drives a sense of moral obligation among teachers to be fair in their behaviour with all students (Hong et al, 2022). The above findings suggest that people with significant levels of empathy, act with kindness because their attitude is influenced by their sense of moral obligation.…”
Section: Empathy Moral Obligations and Social Entrepreneurship Intent...mentioning
confidence: 88%
“…In a multi-country study by Barker et al (2022), conducted on behaviour of nurses towards patients, the authors discovered that the nurses with the best clinical outcomes were those who reported the highest levels of empathy. In addition, a study on empathy of teachers and their fair behaviour with school students shows that empathy drives a sense of moral obligation among teachers to be fair in their behaviour with all students (Hong et al, 2022). The above findings suggest that people with significant levels of empathy, act with kindness because their attitude is influenced by their sense of moral obligation.…”
Section: Empathy Moral Obligations and Social Entrepreneurship Intent...mentioning
confidence: 88%
“…This agrees with the recommendations to evaluate the operationalization of the construct in a specific cultural, social, and professional framework [ 56 , 72 , 73 ], particularly one where prosociality becomes a relevant job skill [ 72 , 73 ] and—in the specific case of the context studied—authenticated by regulatory requirements [ 51 , 52 ]. Although possibly comparable in different degrees and forms of operationalization, the actions of helping [ 36 , 37 ], sharing [ 38 ], caring [ 39 , 40 , 41 ], and feeling empathy [ 32 , 43 , 44 , 45 , 46 , 47 , 48 ] constitute expressions of prosociality in various teaching scenarios, and it is displayed on multiple levels [ 1 ]. One is the micro-intrapersonal, which refers to dispositions and tendencies; another is the meso-intrapersonal, concerning behaviors directed to a person or small groups [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Teacher empathy has been defined as a teacher’s ability to include and share the emotional states of their students [ 43 ], and its relevance as an attribute has been demonstrated [ 44 ]. Greater empathy is related to a better preparation to address bullying [ 45 ], a greater motivation to display fair behaviors with the students [ 46 ], and a greater development of these aspects in the long term [ 47 ]. It can contribute to an increase in intergroup contact and a reduction in conflicts and discrimination in settings of ethnic and cultural diversity [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fairness behavior was measured by the Fairness Behavior Scale [ 42 ]. This scale has 12 items rated by 5 Likert points (1 = totally disagree, 5 = totally agree).…”
Section: Methodsmentioning
confidence: 99%